Polyester film and use thereof
By adopting a polyester film and hard coating with excellent characteristics, the deformation problem of foldable displays under high temperature and repeated bending is solved, image stability and portability are achieved, and the process is simplified and mass-productive.
Patent Information
- Application Number
- CN202380065276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-18
AI Technical Summary
The surface protective film of existing foldable displays is prone to deformation under high temperature environment and repeated bending, resulting in image distortion and visual recognition reduction, and the manufacturing process is complex and lacks mass production.
A new polyester film is adopted, which has a low tan δ value (below 0.020) at 65°C and a high temperature retention angle (below 100°) at 60°C and a thickness of 10 to 80 μm. It meets specific refractive index and density requirements, and a hard coating is arranged on the surface to improve impact resistance.
The polyester film maintains good mechanical and optical properties under high temperature conditions, and is not easy to deform after repeated folding, avoids image disorder, and is simplified in process and is mass-productive. The foldable display equipped with this film provides beautiful images, and is highly convenient for functionality, portability, and so on.
Smart Images

Figure CN119855863A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyester film having excellent heat resistance and bending resistance, a polyester film for a surface protective film for a foldable display, a hard-coated film for a surface protective film for a foldable display, a foldable display and a portable terminal device, and in particular to a polyester film for a surface protective film for a foldable display, a hard-coated film for a surface protective film for a foldable display, a foldable display and a portable terminal device, which are not prone to image disturbance caused by deformation of the film even when repeatedly folded. Background Art
[0002] As the lightweighting of portable terminal devices is promoted, portable terminal devices represented by smartphones have become widely popular. Portable terminal devices are required to have various functions, but also convenience. Therefore, the popular portable terminal devices are required to be easy to operate with one hand and to be stored in the pocket of clothes, so a small screen size of about 6 inches is required.
[0003] On the other hand, tablet terminals with a screen size of 7 to 10 inches are designed to be used not only for video content and music, but also for business purposes, drawing purposes, reading, etc., and have high functionality. However, they cannot be operated with one hand, are not portable, and have problems in terms of convenience.
[0004] In order to achieve this, a method of connecting a plurality of displays to make them compact has been proposed (see Patent Document 1). However, in the invention of Patent Document 1, since the frame portion remains, the image is interrupted, and the reduction in visibility becomes a problem, and it has not yet been popularized.
[0005] On the other hand, in recent years, portable terminals equipped with flexible displays or foldable displays have been proposed. In this case, the image will not be interrupted, and the portable terminal device equipped with a large-screen display can be conveniently carried.
[0006] Here, regarding existing displays and portable terminal devices that do not have a folding structure, the surface of the display can be protected by non-flexible raw materials such as glass. However, in a foldable display, in the case of a display that forms one side through a folded portion, a hard coating film that is flexible and can protect the surface must be used. Plastic films are excellent in flexibility, and polyester films are suitable in terms of mechanical properties, optical properties, price, etc. However, for existing polyester films, when the device itself has heat during operation or when the device is placed in a high temperature environment such as in a car, it may easily cause deformation that distorts the image.
[0007] Furthermore, in a foldable display, since the folded portion is repeatedly bent, there is a problem that deformation occurs over time in the film of this portion, causing distortion of the image of the folded portion displayed on the display.
[0008] Therefore, a method of partially changing the film thickness has also been proposed (see Patent Document 2). However, the invention of Patent Document 2 has a problem that the manufacturing process becomes complicated in order to change the film thickness, and mass productivity is poor.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-228391
[0012] Patent Document 2: Japanese Patent Application Publication No. 2016-155124
[0013] Patent Document 3: International Publication No. 2018 / 150940 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] In addition, a method of adjusting the refractive index of a polyester film in a bending direction has been proposed (see Patent Document 3). However, this film may not be used in applications requiring higher reliability (high temperature region).
[0016] The present invention intends to solve the problems possessed by the surface protection components of existing displays as described above, and in order to provide a foldable display having excellent heat resistance, excellent mass producibility, and less concern about disorder in the image displayed on the folded portion after repeated bending, and a portable terminal device equipped with such a foldable display, the present invention intends to provide: a polyester film for a surface protection film for a foldable display, and a hard coating film for a surface protection film.
[0017] Solutions for solving problems
[0018] The present invention typically includes the following configurations.
[0019] 1. A polyester film, wherein tan δ at 65° C. in at least one of a longitudinal direction and a width direction, as measured by dynamic viscoelasticity under tension, is 0.020 or less.
[0020] 2. The polyester film according to item 1, wherein a high temperature retention angle at 60° C. in at least one of the longitudinal direction and the width direction is 100° or more.
[0021] Here, the high temperature holding angle refers to the angle of the fold produced when the polyester film is fixed under heating at 60° C. for 18 hours so that strain of 1.7% is generated on both surfaces of the bent portion.
[0022] 3. The polyester film according to item 1 or 2, which has a thickness of 10 to 80 μm and satisfies the following conditions.
[0023] (1) The refractive index in either the longitudinal direction or the width direction is 1.590 to 1.650
[0024] (2) The refractive index in the other direction of the length direction and the width direction is 1.670 to 1.700
[0025] (3) The refractive index in the thickness direction is 1.520 or less
[0026] (4) Density 1.380 g / cm 3 above
[0027] 4. The polyester film according to any one of items 1 to 3, which has a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage of 6% or less.
[0028] 5. The polyester film according to any one of items 1 to 4, which is used as a surface protection film for a foldable display.
[0029] 6. The polyester film according to item 5, which has a hard-coat adhesion layer on at least one surface.
[0030] 7. A hard coating film for a surface protection film of a foldable display, comprising: the polyester film according to any one of 1 to 6; and a hard coating layer having a thickness of 1 to 50 μm and located on at least one surface of the polyester film.
[0031] 8. A foldable display, comprising a hard coating film for a surface protection film for the foldable display as described in claim 7, wherein the hard coating film is configured as a surface protection film in such a manner that the hard coating layer is located on the surface of the display, and the hard coating film is configured in the form of a single surface protection film that is continuous through the folding portion of the foldable display.
[0032] 9. A portable terminal device comprising the foldable display described in item 8.
[0033] Effects of the Invention
[0034] The polyester film of the present invention has excellent heat resistance and maintains good mass production performance, and is not easily deformed after repeated folding under high temperature conditions. Even if used in a foldable display, it is not easy to cause image disturbance at the folded part of the display. The polyester film is useful as a surface protection film or a surface protection hard coating film for a foldable display. A foldable display using the surface protection film or the surface protection hard coating film is not easy to deform after repeated folding of these films, and therefore, it is not easy to cause image disturbance at the folded part of the display. A portable terminal device equipped with a foldable display such as the above provides beautiful images, is rich in functionality, and has excellent convenience such as portability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram for illustrating a foldable display and a bending radius when folded.
[0036] Figure 2 It is a schematic diagram for showing the bending direction of the polyester film in the present invention.
[0037] Figure 3 It is a schematic diagram for explaining the method of measuring the high temperature holding angle in the bending direction.
[0038] Figure 4 An enlarged schematic diagram showing a sample film (reference numeral 3) sandwiched between two PTFE plates.
[0039] Figure 5 Schematic diagram showing an outwardly curved foldable smartphone and a foldable display. DETAILED DESCRIPTION
[0040] (monitor)
[0041] The display in the present invention refers to all display devices, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc. For example, LCD, organic EL display, and inorganic EL display having a bendable structure are preferred. Organic EL display and inorganic EL display are more preferred in terms of reducing the layer structure, and organic EL display is particularly preferred in terms of wide color gamut.
[0042] (Foldable Display)
[0043] For a foldable display, a continuous display can be folded into two when carried. By folding to reduce the size by half, portability can be improved. The bending radius of the foldable display is preferably less than 5 mm, and more preferably less than 3 mm. When the bending radius is less than 5 mm, thinning in the folded state becomes possible. It can be said that the smaller the bending radius, the better. If it is a foldable display of the present invention, even if it is used with such a bending radius, the occurrence of creases on the polyester film can be suppressed.
[0044] The bending radius of the foldable display is preferably 0 to 5 mm, more preferably 0 to 3 mm. If the bending radius is 5 mm or less, thinning in the folded state becomes possible. The smaller the bending radius, the better, and it can be 0.1 to 5 mm, 0.1 to 3 mm, 0.5 to 3 mm, 0.5 to 5 mm, 1 to 5 mm. Even if the bending radius is 1 to 5 mm, it can achieve a practically sufficient thinness in the folded state compared to a display without a folding structure.
[0045] The bending radius when folded is Figure 1 In the foldable display 1 in the schematic diagram of , the value obtained by measuring the position indicated by reference numeral 11 is the radius of the inner side of the folded portion when folded. It should be noted that the surface protection film described below may be located outside or inside the fold of the foldable display.
[0046] In addition, the foldable display may be folded in three or four ways, or may be a so-called rollable type, all of which are included in the scope of the foldable display described in the present invention.
[0047] In addition, the polyester film of the present invention can be used not only Figure 1 The foldable display is shown to be bent in both the length direction and the width direction.
[0048] A foldable display can be either outwardly curved or inwardly curved. For an inwardly curved foldable display, the display is located inside when folded, and the display is usually not visually recognizable in the folded state. For an outwardly curved foldable display, the display is located outside when folded, and the display can be visually recognizable in the folded state ( Figure 5 ). The polyester film of the present invention can be used in any manner. In addition, in any foldable display that is curved outward or inward, the polyester film of the present invention can be arranged on either the outside or the inside of the display, or on both the outside and the inside. The polyester film of the present invention is not prone to creases even with a small bending radius, and therefore can be used in such various manners.
[0049] The polyester film for a foldable display of the present invention can be used in any part as long as it is a constituent member of a foldable display. Figure 5 , a diagram schematically showing the structure of a foldable display is shown. Below, taking an organic EL display as an example, a representative structure of a foldable display and a portion in which the polyester film of the present invention can be used are described. It should be noted that, below, the polyester film for a foldable display of the present invention is sometimes referred to as the polyester film of the present invention.
[0050] (Foldable organic EL display)
[0051] The foldable organic EL display has an organic EL component as an essential component, but a circular polarizing plate, a touch panel component, a surface protection film, a back protection film, etc. may be further provided as needed.
[0052] (Organic EL components)
[0053] The general structure of an organic EL component includes: electrode / electron transport layer / luminescent layer / hole transport layer / transparent electrode. As a substrate for providing an electrode, and further providing an electron transport layer, a luminescent layer, a hole transport layer, and a transparent electrode, the polyester film of the present invention can be used. In particular, it can be preferably used as a substrate for a transparent electrode. In this case, the substrate film requires high barrier properties against water vapor and oxygen, so it is preferred that a barrier layer such as a metal oxide layer is provided on the polyester film of the present invention. In order to improve the barrier properties, a plurality of barrier layers can be provided, or a plurality of polyester films provided with barrier layers can be used.
[0054] (Portable terminal device with touch panel)
[0055] In the case of using an organic EL display in a portable terminal device with a touch panel, a touch panel assembly is arranged on the upper part of the organic EL display or between the organic EL layer / phase difference plate. At this time, if an impact is applied from the upper part, there is a concern that the circuit of the organic EL and touch panel will be broken. In order to prevent this, a surface protection film is provided in most cases. The polyester film of the present invention can be used as the surface protection film. The surface protection film includes: a cover window assembled on the outermost surface of the display; an after film (after film) that can be attached, peeled off, and replaced by the user himself, and any of them can use the polyester film of the present invention. When the polyester film of the present invention is used as a surface protection film, it is preferred that a hard coating layer is laminated on at least the surface side of the polyester film. The hard coating layer is located on the visual recognition side, and the polyester film is provided on the surface of the foldable display. It should be noted that the hard coating layer can also be provided on both sides of the polyester film.
[0056] (Surface protection film)
[0057] As the surface protection film, any film having high light transmittance and low haze, such as polyimide film, polyester film, polycarbonate film, acrylic film, triacetyl cellulose film, cycloolefin polymer film, etc., can be used, but among them, polyimide film and polyester film having high impact resistance and sufficient pencil hardness are preferred, and polyester film that can be manufactured inexpensively is particularly preferred.
[0058] (Polyester film)
[0059] The polyester film of the present invention may be a single-layer film or a multilayer film having two or more layers, and each layer constituting the multilayer film may contain the same polyester resin or different polyester resins. In addition, the multilayer film may also have a super multilayer structure formed by alternately and repeatedly stacking different layers. The multilayer film may have a structure of, for example, 2 to 30 layers or 2 to 20 layers. The polyester film may be a single-layer film formed of one or more polyester resins. When two or more polyester resins are used, the polyester film may be a multilayer film having a super multilayer structure or other multilayer films.
[0060] Examples of the polyester resin used in the polyester film include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, such as polyethylene 2,6-naphthalate, or copolymers containing these resins as the main components. Among them, stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, price, etc.
[0061] One mode of polyester film contains polyethylene terephthalate resin as the main component (for example, more than 50% by mass). The polyester film may also contain other polyester resins, and its content relative to the mass of the polyester film 100% by mass, for example, can be less than 50% by mass, less than 40% by mass, less than 10% by mass, preferably less than 5% by mass, more preferably less than 5% by mass. By making the content of other polyester resins less than 5% by mass, the crystallinity of the polyester film can be maintained at a high level, and the high temperature holding angle can be well maintained. When the polyester film contains other polyester resins, its content relative to the mass of the polyester film 100% by mass, for example, can be set to 0.1% by mass or more and less than 50% by mass, 0.1 to 40% by mass, 0.1 to 10% by mass, 0.1 to 5% by mass, 0.1% by mass or more and less than 5% by mass, etc.
[0062] On the other hand, the content of the polyethylene terephthalate resin in the polyester film may be more than 50 mass %, 60 mass % or more, 90 mass % or more, preferably 95 mass % or more, and more preferably more than 95 mass % based on the mass of the polyester film.
[0063] In one embodiment, the ratio of polyethylene terephthalate in the raw material ratio of the polyester film is 100% by weight.
[0064] It should be noted that, in the present invention, the polyester film may include a plurality of polyethylene terephthalates having different properties.
[0065] By increasing the proportion of polyethylene terephthalate, the deformation of the polyester film after folding in a high temperature region is suppressed, and image disturbance at the folded portion of the display can be suppressed. Furthermore, a portable terminal device equipped with a foldable display using the polyester film of the present invention provides a beautiful image and is a device with excellent convenience such as rich functionality and portability.
[0066] When a polyester copolymer is used in a polyester film, as the dicarboxylic acid component of the polyester, for example, aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid; polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. In addition, as the diol component of the polyester, for example, fatty acid diols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol, aromatic diols such as terephthalyl alcohol, alicyclic diols such as 1,4-cyclohexanedimethanol, and polyethylene glycol with an average molecular weight of 150 to 20,000 can be mentioned. The preferred mass ratio of the copolymer component in the polyester copolymer is less than 20 mass%. When it is less than 20 mass%, it is preferred because the film strength, transparency, and heat resistance can be maintained.
[0067] In addition, the intrinsic viscosity of the resin pellets used as the raw material of the polyester film is preferably in the range of 0.50 to 1.0 dl / g. If the intrinsic viscosity is 0.50 dl / g or more, the impact resistance of the obtained film is improved, and it is not easy to cause the internal circuit of the display to be broken due to external impact, which is preferred. If the intrinsic viscosity is 1.00 dl / g or less, the filter pressure increase of the molten fluid will not be excessively increased, making the film manufacturing stable and easy to operate, which is preferred. For example, when the polyester film contains a plurality of resin pellets, the intrinsic viscosity of all of these plurality of resin pellets can be in the range of 0.50 to 1.0 dl / g, and at least one pellet can have an intrinsic viscosity in the range of 0.50 to 1.0 dl / g. In one embodiment, when the polyester film contains a plurality of resin pellets, the intrinsic viscosity of the resin pellets that serve as the main component is in the range of 0.50 to 1.0 dl / g.
[0068] The thickness of the polyester film is preferably 10 to 80 μm, more preferably 25 to 75 μm. If the thickness is 10 μm or more, the pencil hardness improvement effect and impact resistance are improved, and if the thickness is 80 μm or less, it is advantageous for weight reduction and has excellent flexibility, processability, and operability.
[0069] The surface of the polyester film may be smooth or may have projections and depressions. When used for a cover window of a display, it is preferred to have a smooth film surface. The haze of the polyester film is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visual recognition of the image can be improved. The lower limit of the haze is as small as possible, but for the sake of stable production, it is preferably 0.1% or more, and may be 0.3% or more. The haze may be, for example, 0.1-3%, 0.1-2%, 0.1-1%, 0.3-3%, 0.3-2%, 0.3-1%, etc.
[0070] As mentioned above, in order to reduce the haze, it is preferred that the surface roughness of the film is not too large, but from the viewpoint of operability, it may have roughness for the purpose of imparting a certain degree of slip. Such roughness can be formed by a method of mixing particles in a polyester film disposed on the surface layer, a method of coating a coating with particles on a polyester film during film formation, etc.
[0071] As a method for blending particles in a polyester film, a known method can be used. For example, particles can be added at any stage of manufacturing polyester. Preferably, a slurry in which particles are dispersed in ethylene glycol or the like is added at the stage of esterification or after the end of the transesterification reaction and before the start of the polycondensation reaction to promote the polycondensation reaction, thereby blending particles. In addition, particles can be blended by the following methods: a method of blending a slurry of particles dispersed in ethylene glycol or water or the like with a polyester raw material using a mixing extruder with a vent; or a method of blending dried particles with a polyester raw material using a mixing extruder, etc.
[0072] Among them, the following method is preferred as a method of mixing particles: the aggregated inorganic particles are homogeneously dispersed in a monomer solution that becomes a part of the polyester raw material, filtered, and the obtained substance is added to the remaining part of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer solution has a low viscosity, it is easy to homogeneously disperse the particles and filter the slurry with high precision, and when added to the remaining part of the raw material, the dispersibility of the particles is good and new aggregates are not easily generated. From the above viewpoints, it is particularly preferred to homogeneously disperse the inorganic particles in the remaining part of the raw material in a low temperature state before the esterification reaction and then filter.
[0073] Alternatively, after obtaining polyester containing particles in advance, the number of protrusions on the film surface can be further reduced by kneading and extruding the pellets with pellets not containing particles (masterbatch method).
[0074] The tanδ obtained by dynamic viscoelasticity measurement based on stretching in the width direction or length direction of the polyester film is preferably small, and the tanδ at 65°C is preferably 0 to 0.020, and more preferably 0 to 0.018. The tanδ in the dynamic viscoelasticity measurement is obtained from the ratio of the loss modulus to the storage modulus, and the smaller the tanδ, the more the film maintains elasticity. Compared with viscosity, the elasticity is high, and it is not easy to cause irreversible deformation when the elasticity is maintained, and it is not easy to produce creases in the bending resistance.
[0075] Tanδ can also be adjusted according to the stretching ratio and temperature conditions, but it can also be adjusted more effectively by heat treatment (BTA treatment) after film formation. For example, aging and annealing treatment can be cited. As an example of annealing treatment, heating below the Tg of the polyester film, preferably at 60 to 80°C, and more preferably at 65 to 75°C can be cited. By being within the above temperature range, the amorphous region can be effectively changed. At the above temperature, the following treatment is preferably performed: heating for more than 6 hours, preferably more than 12 hours, and more preferably more than 24 hours, and returning to room temperature after more than 1 hour, preferably more than 6 hours, and more preferably more than 12 hours. In addition, when the heating temperature is 70°C, the preferred heating time is more than 12 hours and less than 30 hours, and the preferred cooling rate when returning to room temperature is less than 10°C / hour. By heat treatment after film formation, the amorphous region is made denser, and by approaching the ideal state, the heat resistance is improved. In addition, by the amorphous region being close to the ideal state, the bending resistance is also improved. Therefore, even if the stretching ratio and stretching temperature conditions during production are further increased, a film having excellent bending resistance at high temperatures can be produced.
[0076] The high temperature retention angle in at least one of the width direction and the length direction of the polyester film is preferably 100 to 180°, more preferably 105 to 180°, and even more preferably 110 to 180° under heating conditions at 60°C. If the high temperature retention angle at 60°C is 100° or more, the film is not prone to creases when folded for a long time, and the creases are easy to disappear even if they are produced. Here, the high temperature retention angle refers to the angle of the crease produced after the polyester film is fixed under heating at a predetermined temperature (e.g., 60°C) for 18 hours in a manner that generates a strain of 1.7% on both surfaces of the bent portion.
[0077] By keeping the high temperature holding angle within the above range, deformation at high temperature can be suppressed. In addition, the heat shrinkage rate can be suppressed from increasing, and the dimensional change of the polyester film caused by the heat release of the device can be suppressed. Therefore, according to the present invention, deformation after repeated folding is not easy to occur in the high temperature range, and the image disorder at the folded part of the display can be suppressed. Furthermore, a portable terminal device equipped with a foldable display using the polyester film of the present invention provides beautiful images, is rich in functionality, and has excellent convenience such as portability.
[0078] A sample film (symbol 3) with a width of 10 mm, a flow direction of 50 mm and a thickness of 50 μm is bent with the flow direction as the bending direction and clamped between two PTFE plates (symbol 31) arranged in parallel with a spacer (symbol 32) of 3 mm thickness. After 72 hours in an environment of 20°C and 65% RH, the sample film is taken out and the bending angle (symbol 33) of the sample film after 5 minutes becomes the holding angle.
[0079] It should be noted that the method for measuring the high temperature holding angle in the bending direction is exemplified in the examples.
[0080] The polyester film may contain various additives within a range in which the total light transmittance is maintained within a preferred range. Examples of the additives include antistatic agents, UV absorbers, and stabilizers.
[0081] The total light transmittance of the polyester film is preferably 85% or more, more preferably 87% or more. If the transmittance is 85% or more, visual recognition can be fully ensured. It can be said that the higher the total light transmittance of the polyester film, the better, but from the perspective of stable production, it is preferably 99% or less, and can be 97% or less. The total light transmittance of the polyester film can be 85-99%, 85-97%, 87-99%, 87-97%.
[0082] The maximum heat shrinkage of the polyester film after heat treatment at 150°C for 30 minutes can be 6% or less, preferably 5% or less, and more preferably 2.5% or less. If the maximum heat shrinkage is 6% or less, it is possible to suppress planar defects such as curling and undulation during HC processing. It can be said that the lower the maximum heat shrinkage, the better, but it can be above -1% or above 0%. The negative value here means that expansion occurs after heating. The maximum heat shrinkage can be -1 to 6%, -1 to 5%, -1 to 2.5%, 0 to 6%, 0 to 5%, or 0 to 2.5%.
[0083] One or both surfaces of the polyester film of the present invention may be subjected to treatment for improving adhesion with a resin forming a hard coat layer or the like.
[0084] The treatment for improving adhesion may be, for example, a method of treating the surface of the polyester film, a method of providing an adhesion improving layer on the surface of the polyester film, etc. Examples of the method for treating the surface include sandblasting, roughening treatment by solvent treatment, etc., corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone and ultraviolet irradiation treatment, flame treatment, chromic acid treatment, hot air treatment, etc., and the surface treatment may be used without particular limitation.
[0085] In addition, by sandwiching an adhesion improving layer such as an easy-adhesion layer between the polyester film and the hard coating layer, the adhesion with the resin forming the hard coating layer etc. can also be improved. As the resin forming the easy-adhesion layer, acrylic resin, polyester resin, polyurethane resin, polyether resin etc. can be used without particular limitation, and the easy-adhesion layer can be formed by a common coating method, preferably a so-called in-line coating method.
[0086] The above-mentioned polyester film can be manufactured, for example, through the following steps: a polymerization step, in which the inorganic particles are uniformly dispersed in a monomer solution that becomes a part of the polyester raw material and filtered, and the inorganic particles that become a slurry are added to the remaining part of the polyester raw material to polymerize the polyester; and a film forming step, in which the polyester is melt-extruded into a sheet through a filter, and after cooling, it is stretched to form a substrate film.
[0087] Next, regarding the method for producing a biaxially stretched polyester film, an example of using pellets of polyethylene terephthalate (hereinafter, sometimes referred to as PET) as a raw material for a substrate film is described in detail, but the invention is not limited thereto. In addition, the number of layers such as a single-layer structure and a multi-layer structure is also not limited.
[0088] In addition, in the embodiment using polyethylene naphthalate (PEN) film instead of PET film, the polyester film of the present invention can also be produced by the same method.
[0089] After the PET pellets are mixed and dried in a prescribed ratio, they are supplied to a known melt lamination extruder, extruded from a slit-shaped die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of manufacturing a single-layer film, an unstretched film can be formed with one extruder, and in the case of manufacturing a multi-layer film, two or more extruders, a multi-manifold or a confluence block (e.g., a confluence block with a square confluence portion) can be used to stack a plurality of film layers constituting each outermost layer, extrude a sheet of two or more layers from a nozzle, and cool it on a casting roll to form an unstretched film.
[0090] In the above case, during melt extrusion, it is preferred to perform high-precision filtration to remove foreign matter contained in the resin while the molten resin is maintained at an arbitrary position of about 280° C. The filter material used in the high-precision filtration of the molten resin is not particularly limited, and a filter material made of sintered stainless steel is preferred because it excels in removing aggregates having Si, Ti, Sb, Ge, and Cu as main components and high-melting-point organic matter.
[0091] Furthermore, the filter particle size (initial filtration efficiency 95%) of the filter material is preferably less than 20 μm, particularly preferably less than 15 μm. When the filter particle size (initial filtration efficiency 95%) of the filter material exceeds 20 μm, foreign matter larger than 20 μm cannot be fully removed. By using a filter material having a filter particle size (initial filtration efficiency 95%) of less than 20 μm for high-precision filtration of molten resin, productivity may sometimes be reduced, but it is preferred in terms of obtaining a film with fewer protrusions generated by coarse particles.
[0092] (About refractive index)
[0093] The preferred refractive index when using a polyester film as a surface protective film for a foldable display is described, but the film of the present invention is not limited to the following. The refractive index of at least one of the length direction (mechanical flow direction) and the width direction of the polyester film is preferably 1.590 to 1.650, more preferably 1.591 to 1.649, further preferably 1.591 to 1.610, and further preferably 1.591 to 1.606. If the refractive index in at least one of the length direction and the width direction is 1.590 to 1.650, there is less deformation during repeated folding, and there is no worry about reducing the image quality of the foldable display, which is preferred.
[0094] The polyester film preferably uses a direction with a refractive index of 1.590 to 1.650 as the refraction direction. Here, the bending direction is Figure 2 The direction indicated by symbol 22 on the polyester film (symbol 2) is a direction orthogonal to the folding portion (symbol 21) envisioned in the use of the surface protection film for a foldable display. The refractive index is more preferably 1.591 to 1.649. Of course, this direction is preferably the aforementioned bending direction. When the refractive index is 1.590 or more, the occurrence of cracks or, in the worst case, breakage in the direction of the folding portion after the bending test can be suppressed, and therefore, the visual recognition of the display is not easily hindered.
[0095] The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and the stretching temperature. In addition, in order to adjust the refractive index, a relaxation process and multi-stage stretching in the stretching direction can also be used. In the case of multi-stage stretching, it is preferred that the stretching ratio after the second stage is higher than the stretching ratio in the first stage.
[0096] By controlling the refractive index of at least one of the length direction (mechanical flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index of the bending direction within the above range, the fatigue caused by the compressive stress applied to the inside during folding can be reduced. It is believed that the fatigue caused by the compressive stress mainly occurs in the crystal part, and when there are few crystals in the bending direction, fatigue is not easy. Therefore, by making the refractive index in the bending direction smaller than the refractive index in the direction perpendicular to the bending direction, the amount of oriented crystals in the bending direction can be reduced, and the fatigue caused by the compressive stress can be suppressed.
[0097] In addition, the creep phenomenon caused by the tensile stress applied to the outside of the fold during folding can be suppressed by reducing the refractive index. It is believed that fatigue caused by tensile stress mainly occurs in the amorphous part, and the alignment of the molecular chains occurs due to the repeated application of stress, resulting in deformation. It can be inferred that when there are fewer molecular chains arranged in the bending direction, the deformation caused by alignment is less. In addition, when there are fewer amorphous parts, fatigue caused by stretching can be suppressed, so it is preferred that the crystallinity, that is, the density, is high.
[0098] In the present invention, for the unstretched polyester sheet, the stretching ratio in at least one of the longitudinal direction (mechanical flow direction) and the width direction is preferably set to 1.2 to 4.0 times, more preferably 1.4 to 3.5 times, and further preferably 1.7 to 2.0 times. Moreover, when the polyester film is used for a foldable display, the stretching direction given the ratio is preferably a bending direction. If the stretching ratio is 1.2 times or more, the deformation during the hard coating is suppressed, so it is preferred. If the stretching ratio is 4.0 times or less, the thickness of the film does not vary, so it is preferred. As the stretching temperature, 75 to 120°C is preferred, and 75 to 105°C is further preferred. It should be noted that the heating method during stretching can adopt the previously known means such as hot air heating, roller heating, infrared heating, etc. By setting the stretching temperature to 75 to 120°C, the large thickness unevenness caused by stretching at the above-mentioned stretching ratio can be prevented. In addition, by stretching at a low temperature as much as possible, the refractive index Nz in the thickness direction can be reduced.
[0099] (Refractive index in the folded direction)
[0100] The refractive index of the polyester film in a direction orthogonal to the direction in which the refractive index is 1.590 to 1.650 is preferably 1.670 to 1.700. For example, the refractive index of the polyester film in the bending direction is preferably 1.590 to 1.650, and the refractive index in the direction orthogonal to the bending direction (the direction of the folded portion) is preferably 1.670 to 1.700. By setting the refractive index in the folded portion direction to 1.670 to 1.700, deformation during folding along the bending direction can be reduced. By setting the refractive index in the folded portion direction to 1.700 or less, cracks or breaks in the direction of the folded portion can be suppressed. By setting the refractive index in the folded portion direction to 1.670 or more, the bendability in the bending direction can be improved, and the surface hardness of the hard coating layer when a hard coating layer is laminated on the film can be improved. The refractive index in the folded portion direction is more preferably 1.675 to 1.695.
[0101] For example, when the longitudinal direction of the polyester film is the bending direction, the direction (folded portion direction) perpendicular to the bending direction corresponds to the width direction of the polyester film.
[0102] The refractive index in the direction perpendicular to the bending direction is preferably 1.670 to 1.700, more preferably 1.675 to 1.695.
[0103] When comparing the refractive index in the bending direction and the refractive index in the direction orthogonal to the bending direction (the folding direction), it is desirable that the refractive index in the bending direction is lower. The refractive index in the bending direction is lower than the refractive index in the folding direction, thereby reducing deformation when folding along the bending direction. In addition, the occurrence of cracks in the folding direction can be suppressed, and fracture can be further suppressed. On this basis, fracture in the winding process after stretching can be suppressed. In addition, the density can be increased, and the high temperature holding angle can be improved.
[0104] As a method for adjusting the refractive index in the direction perpendicular to the bending direction, there can be cited methods of adjusting the stretching ratio in the direction, the stretching preheating temperature, the stretching temperature, multi-stage stretching, film relaxation, etc. The stretching ratio in the direction perpendicular to the bending direction is preferably 4.0 to 6.0 times. In addition, the stretching preheating temperature in the direction perpendicular to the bending direction is preferably 70 to 110°C. When multi-stage stretching is performed in a direction perpendicular to the bending direction, it is preferred that the stretching ratio in the second stage and thereafter is higher than the stretching ratio in the first stage. Film relaxation can be performed at 1 to 10% in either the mechanical flow direction (length direction) or the perpendicular direction (width direction).
[0105] (Refractive index in the thickness direction)
[0106] The refractive index in the thickness direction is preferably 1.520 or less. By making the refractive index in the thickness direction 1.520 or less, even if the refractive index in the bending direction is designed to be low, the reduction in the hardness of the film surface can be suppressed, and the bendability and surface hardness can be taken into account. By making the refractive index in the thickness direction 1.520 or less, the indentation depth after the test force is unloaded is reduced, and the surface hardness of the hard coating layer when the hard coating layer is laminated on the film can be improved. The lower the refractive index in the thickness direction, the better, but in terms of stable production, it is preferably 1.300 or more, and further can be 1.400 or more. The refractive index in the thickness direction can be 1.300 to 1.520, 1.400 to 1.520. The above range can be simply achieved by gradually increasing the stretching ratio in both the bending direction and the folding direction, but in terms of controlling the refractive index in the bending direction and the width direction within the preferred range, in order to control the refractive index in the thickness direction, the balance in each process of the film-making process is important.
[0107] The methods for controlling the refractive index in the thickness direction within the above range include: stretching preheating temperature in the bending direction, stretching temperature, stretching ratio, stretching preheating temperature in the direction of the folding portion, stretching temperature, multi-stage stretching, high-ratio stretching or thermal fixing. The stretching preheating temperature in the bending direction is preferably 70°C to 110°C. The stretching temperature in the bending direction is preferably 75 to 120°C. By lowering the stretching temperature and stretching at a low stretching ratio, the refractive index in the thickness direction can be effectively reduced while maintaining the bending property in the bending direction. The stretching preheating temperature in the folding direction is also preferably 75°C to 110°C. The stretching temperature is preferably 75 to 120°C. The stretching ratio in the folding direction is preferably 4.0 to 6.0 times, which can maintain or reduce the refractive index in the bending direction while effectively reducing the refractive index in the thickness direction. As a high-ratio stretching method, multi-stage stretching can be used. In addition, a method of stretching again after the crystallization step can also be used. Accelerated stretching in which the stretching speed is increased from the initial stretching to the second half can also be used.
[0108] The heat setting temperature is preferably 180 to 240° C. By heat setting, oriented crystallization in the stretching direction proceeds, and the refractive index in the thickness direction can be reduced.
[0109] The reason why the surface hardness of a hard coating layer is improved when the hard coating layer is stacked on a thin film by lowering the refractive index in the thickness direction is uncertain, but it can be considered that aromatic groups such as benzene rings in the molecular chain are oriented in the plane direction, which has the effect of suppressing deformation caused by stress applied in the thickness direction.
[0110] (About the density of polyester film)
[0111] The density of the polyester film is preferably 1.380 g / cm 3 More preferably 1.383 g / cm3 By making the density 1.380g / cm 3 The above density can fully crystallize the polyester film and suppress deformation of the polyester film at 60°C. In addition, the heat shrinkage rate can be suppressed and the dimensional change of the polyester film caused by heat release of the device can be suppressed. The higher the density, the better, but it can be 1.400 g / cm 3 The density can be 1.380~1.400g / cm 3 1.383~1.400g / cm 3 By setting the heat setting temperature to 180 to 240° C., crystallization can be advanced and the density can be increased.
[0112] When a polyester film is used as a surface protective film for a foldable display, the bending direction of the polyester film preferably corresponds to the length direction (mechanical flow direction). As a result, it is easy to reduce the refractive index in the bending direction during biaxial stretching, and it is easy to improve the bendability. That is, the unstretched polyester sheet is stretched along the length direction at a stretching ratio of 1.2 to 4.0 times, more preferably 1.4 to 3.5 times, and further preferably 1.7 to 2.0 times, thereby obtaining a polyester film that is preferably used as a surface protective film for a foldable display. Moreover, it can be said that stretching along the width direction at a stretching ratio of 4.0 to 6.0 times is a preferred method.
[0113] In order to adjust film forming properties, film strength, thermal dimensional stability, appearance defects, etc., any film forming method such as stretching, relaxation, thermal fixation, surface treatment, etc. can be adopted. By controlling the refractive index and density of the film within the above preferred ranges, a film suitable for foldable displays with excellent bendability and surface hardness can be provided.
[0114] Specifically, for example, after the PET pellets are fully vacuum dried, they are supplied to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 1.2 to 4.0 times in the length direction with a roller heated to 75 to 120°C to obtain a uniaxially oriented PET film. The ends of the film are gripped with a clamp and introduced into a hot air zone heated to 75 to 120°C. After drying, it is stretched to 4.0 to 6.0 times in the width direction. Next, it is introduced into a heat treatment zone at 180 to 240°C and heat treated for 1 to 60 seconds to produce a polyester film. In this heat treatment process, a relaxation treatment of 0 to 10% can also be performed in the width direction or the length direction as needed.
[0115] The intrinsic viscosity of the polyester film is preferably in the range of 0.50 to 1.0 dl / g. If the intrinsic viscosity is 0.50 dl / g or more, the impact resistance is improved, and it is not easy to cause the internal circuit of the display to be disconnected due to external impact, which is preferred. On the other hand, if the intrinsic viscosity is 1.00 dl / g or less, the filter pressure of the molten fluid will not increase excessively, making the film production stable and easy to operate, which is preferred.
[0116] (Easy Adhesion Layer)
[0117] In order to improve the adhesion between the polyester film and the hard coating layer, etc., it is also preferred to laminate an easy-adhesive layer on at least one side of the polyester film of the present invention. The easy-adhesive layer can be obtained as follows: After applying the coating liquid for forming the easy-adhesive layer on one side or both sides of an unstretched or longitudinally uniaxially stretched film, heat-treating and drying at 100 to 150°C as needed, and further stretching in at least one direction that has not been stretched, the easy-adhesive layer can be obtained. Heat treatment and drying can also be performed after biaxial stretching. The final coating amount of the easy-adhesive layer is preferably managed to be 0.005 to 0.20 g / m 2 If the coating amount is 0.005g / m 2 On the other hand, if the coating amount is 0.20 g / m 2 Below, the anti-blocking property is improved, which is preferred.
[0118] As the resin contained in the coating liquid used in the lamination of the easy-adhesive layer, for example, polyester resin, polyether polyurethane resin, polyester polyurethane resin, polycarbonate polyurethane resin, acrylic resin, etc. can be used without particular limitation. As the cross-linking agent contained in the coating liquid for forming the easy-adhesive layer, melamine, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. can be listed. Two or more kinds can be mixed and used respectively. They are preferably coated with water-based coating liquid in terms of the properties of online coating. The aforementioned resin and cross-linking agent are preferably water-soluble or water-dispersible resins or compounds.
[0119] In order to give the easy-adhesive layer easy slip, preferably add particles. The average particle size of the particles is preferably less than 2 μm. When the average particle size of the particles is less than 2 μm, the particles become difficult to fall off from the easy-adhesive layer. As the particles contained in the easy-adhesive layer, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, calcium fluoride, styrene-based, acrylic acid-based, melamine-based, benzoguanamine-based, silicone-based organic polymer-based particles, etc. can be listed. They can be added in the easy-adhesive layer alone, or two or more can be combined to add.
[0120] In addition, as the method of applying the coating solution for forming the easy-adhesive layer, a known method can be used. For example, reverse roll coating, gravure coating, kiss coating, roller brushing, spraying, air knife coating, wire rod coating, tubular scraper method, etc. can be listed, and these methods can be carried out alone or in combination.
[0121] (Hard Coating)
[0122] When the polyester film of the present invention is used as a surface protection film located on the surface of a foldable display to protect the display, it is preferred that at least one surface thereof has a hard coating layer. In the display, the hard coating layer is preferably located on the display surface side of the polyester film and used. As the resin forming the hard coating layer, resins such as acrylic acid, siloxane, inorganic mixture, urethane acrylate, polyester acrylate, and epoxy can be used without particular limitation. In addition, two or more materials can be used in combination, and particles such as inorganic fillers and organic fillers can also be added.
[0123] (Film thickness of hard coat layer)
[0124] The film thickness of the hard coating layer is preferably 1 to 50 μm. If it is 1 μm or more, it is fully cured and the pencil hardness becomes high, which is preferred. In addition, by making the thickness less than 50 μm, the curling caused by the curing shrinkage of the hard coating layer can be suppressed, and the operability of the film can be improved.
[0125] (Coating method)
[0126] As the coating method of the hard coat layer, a Meyer bar, a gravure coater, a rod coater, a knife coater, etc. can be used without particular limitation, and it can be appropriately selected according to the viscosity and the film thickness.
[0127] (Curing conditions)
[0128] As a method for curing the hard coat layer, a curing method using energy rays such as ultraviolet rays, electron beams, or heat can be used. As a curing method, curing using energy rays such as ultraviolet rays, electron beams, etc. is preferred in order to reduce damage to the film.
[0129] (Characteristics of hard coating)
[0130] The hard coat layer in the present invention can be used for the purpose of increasing the pencil hardness of the surface as described above and protecting the display, and preferably has a high transmittance. As a film having a hard coat layer (sometimes referred to as a hard coat film), the total light transmittance is preferably 87% or more, and more preferably 88% or more. If the total light transmittance is 87% or more, sufficient visual recognition can be obtained. The total light transmittance of the hard coat film is generally higher, the more preferred, but for the sake of stable production, it can be 99% or less, 97% or less. The total light transmittance of the hard coat film can be 87-99%, 88-99%, 87-98%, 88-98%. In addition, the haze of the hard coat film is generally preferably low, preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visual recognition of the image can be improved. For the sake of stable production, the haze is preferably 0.1% or more, and can be 0.3% or more. The haze of the hard coating film may be 0.1-3%, 0.1-2%, 0.1-1%, 0.3-3%, 0.3-2%, or 0.3-1%.
[0131] The hard coating layer may be further provided with other functions. For example, a hard coating layer provided with functions such as an anti-glare layer having a constant pencil hardness as described above, an anti-glare anti-reflection layer, an anti-reflection layer, a low-reflection layer, and an antistatic layer may be preferably used in the present invention.
[0132] Example
[0133] Next, the present invention will be described using examples and comparative examples. First, the following describes a method for determining characteristic values implemented in the following examples.
[0134] (1) Intrinsic viscosity
[0135] The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). The solution was centrifuged to remove inorganic particles, and then the flow time of the solution with a concentration of 0.4 (g / dl) and the flow time of the solvent alone were measured at 30°C using an Ubbelohde viscometer. From the ratio of these time, the intrinsic viscosity was calculated using the Huggins formula, assuming that the Huggins constant was 0.38.
[0136] (2) Dynamic viscoelasticity measurement of polyester film
[0137] The measurement was carried out in a dynamic viscoelasticity measuring device "DMA7100" (manufactured by Hitachi High-Tech Corporation) in a tensile mode with a sample size of 8 mm in width and 20 mm in chuck spacing. The temperature was raised at 10°C / min at a frequency of 1 Hz and a measuring temperature of 25°C to 150°C. The tanδ value was plotted as tanδ=loss modulus / storage modulus, and then the tanδ at 65°C was read.
[0138] (3) High temperature holding angle
[0139] The angle of the folded line generated when the polyester film was fixed so as to apply a strain of 1.7% to both surfaces of the bent portion was measured.
[0140] Figure 3 This is a schematic diagram for illustrating the method of measuring the high temperature holding angle in the bending direction. The sample film (symbol 3) is cut into 10 mm in the width direction and 50 mm in the mechanical flow direction. A PTFE plate (symbol 32) as a spacer is clamped between two PTFE plates (symbol 31) to form a space. In the case of a 50 μm thick sample film, the thickness of the spacer is set to 3 mm. Double-sided tape is pasted on both ends of the sample film in the mechanical flow direction so that the mechanical flow direction is the bending direction. The film is clamped in a bent state in a gap of 3 mm formed between two PTFE plates, and both ends are fixed to the two PTFE plates (symbol 31) with double-sided tape. After being placed in a dry environment at 60°C for 18 hours, it is taken out from between the two PTFE plates (symbol 31). After 5 minutes, the angle (symbol 33) of the crease generated in the film is measured. This angle is set as the high temperature holding angle.
[0141] In order to make the strain constant, the thickness of the PTFE plate used as a spacer was changed according to the thickness of the film (reference numeral 32).
[0142] Figure 4 Shown is sandwiched between two PTFE plates ( Figure 3 The enlarged schematic diagram of the sample film (symbol 3) in the state between the symbol 31). It should be noted that, Figure 4 In the figure, symbol 41 is the diameter of the semicircle of the outermost surface of the sample film, symbol 42 is the diameter of the semicircle of the neutral plane of the sample film, and symbol 43 is the diameter of the semicircle of the innermost surface of the sample film. The neutral plane to which neither the compressive stress nor the tensile stress is applied is defined as the center in the thickness direction (dashed line in the figure), and the difference between the neutral plane and the two surfaces is defined as strain.
[0143] That is, in the evaluation of the high temperature holding angle, the strain (1.7%) can be expressed by the following method.
[0144] Strain (1.7%)
[0145] =(|semicircle of the outermost surface or the innermost surface - semicircle of the neutral surface| / semicircle of the neutral surface)×100 Here, the semicircle can be calculated from the thickness of the sample film t (mm), the bending diameter (the diameter of the outermost surface, that is, the thickness of the spacer used) d (mm), and the following formulas.
[0146] The semicircle of the outermost surface = d × π / 2
[0147] The semicircle of the neutral plane = (dt) × π / 2
[0148] The innermost semicircle = (d-2t) × π / 2
[0149] Based on the above, when the strain is set to 1.7%, the spacer thickness (mm) is determined from the sample film thickness t (mm) and the bending diameter (spacer thickness) d (mm) by the following formula. The typical spacer thickness relative to the film thickness is expressed as follows.
[0150] Spacer thickness d (mm) = film thickness (mm) × 60
[0151] For example, in the case of the sample film having a thickness of 50 μm, the diameter of the outermost surface (symbol 41) is the same as the thickness d of the spacer, which is 3 mm. The diameter of the innermost surface (symbol 43) is 2.9 mm, and the diameter of the neutral plane (symbol 42) is 2.95 mm. Here, in the above formula representing strain, the semicircle of the outermost surface and the semicircle of the innermost surface can be appropriately selected.
[0152] Representative spacer thickness (d) relative to film thickness (t) are shown below.
[0153] Film thickness (t) Spacer thickness (d)
[0154]
[0155] (4) Bending resistance of polyester film (bending radius 1.5 mm)
[0156] Prepare a polyester film sample with a size of 20mm in the width direction (TD) and 110mm in the machine flow direction (MD). Use a no-load U-shaped stretch tester (made by Yuasa System Equipment Co., Ltd., DLDMLH-FS), set the bending radius to 1.5mm, and bend 200,000 times at a speed of 1 time / second. At this time, for the sample, the position of 10mm at both ends of the long side is fixed, and the bending part is set to 20mm×90mm. In this test, Figure 1In the foldable display shown, a polyester film is arranged on the inner side of the folded portion, and the display bending radius is set to 1.5 mm. The display is folded repeatedly. After the predetermined number of bends are completed, the sample is placed on a flat surface with the inner side of the bend facing downward, and visual inspection and observation using a digital microscope (RH8800 manufactured by HIROX Corporation) at 700 times magnification are performed.
[0157] ○: There are no cracks or creases in the sample, and the maximum height of the floating surface when placed on a horizontal plane is less than 3 mm.
[0158] △: There are no cracks in the sample. When placed on a horizontal plane, the maximum height of the floating is less than 5 mm.
[0159] ×: The sample has cracks or creases, and when placed on a horizontal surface, the maximum height of the floating is 5 mm or more.
[0160] (5) Refractive index of polyester film
[0161] The refractive index in the longitudinal direction, the refractive index in the width direction, and the refractive index in the thickness direction were determined using an Abbe refractometer (NAR-4T manufactured by ATAGO CO., LTD., measuring wavelength 589 nm) in accordance with JIS K 7142-2008 “Method for determination of refractive index of plastics (Method A)”.
[0162] (6) Total light transmittance and haze of hard coating film
[0163] The polyester film after hard coating was used as a sample, and the total light transmittance and haze were measured using a haze meter (NDH5000 manufactured by Nippon Denshoku Industries Co., Ltd.).
[0164] (7) Density of polyester film
[0165] The density of the polyester film was measured by the method based on JIS K-7112-1999 (density gradient tube method). (Unit: g / cm 3 ).
[0166] (8) Maximum thermal shrinkage of polyester film
[0167] Cut the sample film into 10mm in length and 250mm in width, align the long side with the direction to be measured, apply marks at intervals of 200mm, and measure the distance A (mm) between the marks under a constant tension of 5g. Next, place the sample film in an oven at 150°C for 30 minutes without load, take it out of the oven, and cool it to room temperature. After that, calculate the distance B (mm) between the marks under a constant tension of 5g, and calculate the thermal shrinkage rate (%) according to the following formula. It should be noted that the above-mentioned distance A and distance B are measured at three equal positions along the width direction of the sample film, and the average value of the distance A and distance B at the three points is rounded to the second decimal place.
[0168] Thermal shrinkage (%) = [(AB) × 100] / A
[0169] For the same film, the thermal shrinkage of the sample film with the bending direction as the long side and the thermal shrinkage of the sample film with the folded part direction (direction perpendicular to the bending direction) as the long side were measured, and the larger thermal shrinkage was defined as the maximum thermal shrinkage (%).
[0170] (Preparation of polyethylene terephthalate (PET) pellets (a))
[0171] As the esterification reaction apparatus, a continuous esterification reaction apparatus composed of a stirring device, a partial condenser, and a three-stage complete mixing tank having a raw material inlet and a product outlet was used. TPA was 2 tons / hour, EG was 2 mols per 1 mol of TPA, and antimony trioxide was set to an amount of 160 ppm of Sb atoms with respect to the produced PET. These slurries were continuously supplied to the first esterification reaction vessel of the esterification reaction apparatus, and reacted at 255° C. at an average residence time of 4 hours under normal pressure. Next, the reaction product in the first esterification reaction vessel was continuously taken out of the system and supplied to the second esterification reaction vessel. EG distilled from the first esterification reaction vessel was supplied to the second esterification reaction vessel in an amount of 8 mass % relative to the produced polymer (produced PET). Furthermore, an EG solution containing magnesium acetate in an amount of 65 ppm of Mg atoms with respect to the produced PET and an EG solution containing TMPA in an amount of 20 ppm of P atoms with respect to the produced PET were added, and reacted at 260° C. at an average residence time of 1.5 hours under normal pressure. Next, the reaction product in the second esterification reactor was continuously taken out of the system and supplied to the third esterification reactor, and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the generated PET was further added, and the reaction was carried out at 260° C. under normal pressure with an average residence time of 0.5 hours. The esterification reaction product generated in the third esterification reactor was continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, and then filtered with a stainless steel sintered body filter (nominal filtration accuracy 5 μm particles 90% cutoff) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.
[0172] (Polymerization of urethane resin)
[0173] In a four-necked flask equipped with a stirrer, a DiMuro reflux condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 72.96 parts by mass of 1,3-bis(isocyanatomethyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol with a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as solvents were added, and stirred for 3 hours at 75°C under a nitrogen atmosphere to confirm that the reaction liquid reached the specified amine equivalent. Then, after cooling the reaction liquid to 40°C, 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450 g of water was added to a reaction container equipped with a high-speed stirring homogenizer, and the temperature was adjusted to 25°C, while stirring at 2000 min. -1 The isocyanate group-terminated prepolymer was added while stirring and mixing to disperse in water. Then, acetonitrile and part of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35% by mass.
[0174] (Polymerization of water-soluble carbodiimide compounds)
[0175] In a flask equipped with a thermometer, a nitrogen inlet tube, a reflux condenser, a dropping funnel and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phosphole-1-oxide as a carbodiimidization catalyst were added, and stirred at 180° C. for 10 hours under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Then, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100° C. for 24 hours. Water was slowly added thereto at 50° C. to obtain a yellow transparent water-soluble carbodiimide compound (B) having a solid content of 40% by mass.
[0176] (Preparation of coating liquid for forming an easily adhesive layer)
[0177] The following coating materials were mixed to prepare a coating solution.
[0178]
[0179] (Silica sol with an average particle size of 40 nm and a solid content concentration of 40% by mass)
[0180] Surfactant 0.05 parts by mass
[0181] (Silicone-based, solid content concentration 100% by mass)
[0182] (Preparation of Hard Coating Liquid a)
[0183] 0.1 parts by weight of a leveling agent (BYK307, manufactured by BYK Japan KK, concentration 100%) was added to 100 parts by weight of a hard coating material (Opstar Z7503, manufactured by JSR Corporation, concentration 75%), and the mixture was diluted with methyl ethyl ketone (MEK) to prepare a hard coating liquid a having a solid content concentration of 40% by weight.
[0184] (Example 1)
[0185] The pellets (a) of polyethylene terephthalate are supplied to an extruder and melted at 285°C. The polymer is filtered with a filter material of a stainless steel sintered body (nominal filtration accuracy 10μm particles 95% cutoff), extruded from a nozzle into a sheet, and then, by an electrostatic casting method, contacted with a casting drum with a surface temperature of 30°C, cooled and solidified to produce an unstretched film. The unstretched film is uniformly heated to 75°C with a heating roller, heated to 85°C with a non-contact heater, and 1.4 times of roller stretching (longitudinal stretching) is performed. The obtained uniaxially stretched film is introduced into a tenter, preheated at 105°C, stretched to 4.0 times in the transverse direction at 95°C, fixed in width, heat treated at 230°C for 5 seconds, and further relaxed by 4% in the width direction at 180°C, thereby obtaining a polyethylene terephthalate film with a thickness of 50μm.
[0186] The obtained film was heated at 70° C. for 24 hours and cooled to room temperature of 25° C. at 2° C. / hour over 22.5 hours to obtain a sample.
[0187] (Examples 2 to 9)
[0188] A polyester film sample was produced in the same manner as in Example 1 at the stretching ratio, MD stretching temperature, TD preheating temperature, and heat setting temperature described in Table 2.
[0189] (Comparative Examples 1 to 4)
[0190] Except that the 70° C. heat treatment (BTA treatment) after film formation was not performed, the same polyester film samples as in Examples 1 to 4 were obtained.
[0191] (Comparative Examples 5 to 6)
[0192] A polyester film sample was obtained in the same manner as in Examples 1 and 4 except that the heating temperature in the BTA treatment after film formation was 90°C.
[0193] (Comparative Example 7)
[0194] A polyester film sample similar to that of Example 4 was obtained except that the heating time in the BTA treatment after film formation was set to 1 hour and the film was taken out directly from the heating oven without taking a cooling time after heating.
[0195] (Manufacturing of Hard Coat Film (HC Film))
[0196] The hard coating solution a was applied to one surface of the polyester film sample prepared in the examples and comparative examples using a Meyer bar so that the film thickness after drying was 5 μm, and after drying at 80° C. for 1 minute, ultraviolet rays (accumulated light intensity 200 mJ / cm 2 ) to obtain a hard-coated film having a hard-coat layer laminated on one side of a polyester film.
[0197] (Hard-coated film mounted foldable mobile communication device)
[0198] The surface of the hard coating film not laminated with the hard coating layer was bonded to an organic EL device via a 25 μm thick adhesive layer to produce a smartphone-type foldable display that can be folded in half at the center of the whole. Figure 1 The bending radius of the symbol 11 in is 3 mm. The hard coating film is arranged as a surface protection film on the surface of a display that is continuous via a folded portion, and the hard coating film is arranged in such a way that the hard coating layer is located on the surface (visual recognition side) of the display. The foldable display using the hard coating film of each embodiment satisfies the action and visual recognition of a portable smartphone that can be folded in half in the center. In addition, the surface is not dented by external force.
[0199] On the other hand, for the hard coating films of the comparative examples, in the foldable display used in the same manner, as the frequency of use increases, the image deformation is felt to gradually occur at the folding portion of the display, which is not preferred. In addition, there are also cases where depressions and scratches are confirmed on the surface of the folding portion.
[0200] [Table 1]
[0201]
[0202] [Table 2]
[0203]
[0204] Industrial Applicability
[0205] According to the foldable display using the polyester film or hard coating film of the present invention, mass production is maintained, and the polyester film or hard coating film on the surface of the foldable display does not deform after repeated folding, so that image disturbance does not occur at the folded portion of the display. A portable terminal device or image display device equipped with a foldable display using the polyester film or hard coating film of the present invention as a surface protection film provides beautiful images, is rich in functionality, and has excellent convenience such as portability.
[0206] Description of Reference Numerals
[0207] 1: Foldable display
[0208] 11: Bending radius
[0209] 2: Polyester film for surface protection film of foldable display
[0210] 21: Folding part
[0211] 22: Bending direction (direction perpendicular to the folded portion)
[0212] 3: Sample film
[0213] 31: PTFE sheet
[0214] 32: Spacer
[0215] 33: Keep Angle
[0216] 41: The diameter of the outermost surface
[0217] 42: Diameter of the neutral plane
[0218] 43: The diameter of the innermost surface
[0219] 5. Foldable display
[0220] 51: rear film
[0221] 52: Cover window (surface protection film)
[0222] 53: Polarizing plate / anti-reflection component
[0223] 54: Touch panel components
[0224] 55: Organic EL components
[0225] 56: Back protective film
[0226] 6: Outward-bending foldable smartphone
Claims
1. A polyester film, wherein tan δ at 65° C. in at least one of a longitudinal direction and a width direction, as measured by dynamic viscoelasticity under tension, is 0.020 or less.
2. The polyester film according to claim 1, wherein the high temperature retention angle at 60°C in at least one of the longitudinal direction and the width direction is 100° or more, Here, the high temperature holding angle refers to the angle of the fold produced when the polyester film is fixed under heating at 60° C. for 18 hours so that strain of 1.7% is generated on both surfaces of the bent portion.
3. The polyester film according to claim 1, characterized in that The thickness is 10 to 80 μm and meets the following conditions: (1) The refractive index in either the longitudinal direction or the width direction is 1.590 to 1.650, (2) The refractive index in the other direction of the length direction and the width direction is 1.670 to 1.700, (3) The refractive index in the thickness direction is 1.520 or less, (4) Density 1.380 g / cm 3 above.
4. The polyester film according to claim 1, which has a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage of 6% or less. The polyester film according to claim 1 , which is used as a surface protection film for a foldable display. The polyester film according to claim 5 , comprising an easy-adhesion layer on at least one surface.
7. A hard coating film for a surface protection film of a foldable display, comprising: the polyester film according to any one of claims 1 to 6; and a hard coating layer having a thickness of 1 to 50 μm and located on at least one surface of the polyester film.
8. A foldable display, comprising a hard coating film for a surface protection film for a foldable display according to claim 7, wherein the hard coating film is configured as a surface protection film in such a way that a hard coating layer is located on the surface of the display, and the hard coating film is configured in the form of a single surface protection film that is continuous through a folded portion of the foldable display.
9. A portable terminal device comprising the foldable display according to claim 8.
Citation Information
Patent Citations
Method of processing hard coat film, hard coat film and protective film
JP2010228391A
Manufacturing method for foldable hard coating film
JP2016155124A
Polyester film and applications thereof
WO2018150940A1